Microstructures and mechanical properties of hemp fabrics reinforced organoclay-cement nanocomposites - Hakamy, A.; Shaikh, Faiz; Low, It Meng (Elsevier BV, 2013)
Cement eco-nanocomposites reinforced with hemp fabric (HF) and nanoclay platelets (Cloisite30B) arefabricated and investigated in terms of XRD, SEM, physical and mechanical properties. Results indicated that the mechanical properties generally increased as a result of the addition of nanoclay into the cement matrix with and without HF. An optimum replacement of ordinary Portland cement by 1 wt% nanoclay is concluded from the current work. It is found that, 1 wt% nanoclay decreases the porosity and also significantly increases the density, flexural strength and fracture toughness of cement composite and HF reinforced nanocomposite. The microstructural analysis results indicate that the nanoclay behaves not only as a filler to improve microstructure, but also as an activator to promote pozzolanic reaction which modified cement matrix and improved the hemp fabric-matrix adhesion. The failure micromechanisms and energy dissipative processes in HF reinforced cement composite and nanocomposite are discussed in terms of microstructural observations.